A laboratory screening of three species of seaweeds in Cancabato Bay, Tacloban, Leyte for antibacterial property - Cañete, Edwin Jadulco (Division of Natural Sciences and Mathematics, University of the Philippines Visayas Tacloban College, 1998)
Further phytochemical study to isolate and identify the active components of P. minor and L. pavillosa and toxicity testing of the extracts are highly recommended